Long-acting amylin analogues for the management of obesity. Issue 2 (21st April 2022) - Mathiesen, David S.; Bagger, Jonatan I.; Knop, Filip K.
Abstract : Purpose of review: To summarize recent developments of long-acting amylin analogues for the treatment of obesity and to outline their mode of action. Recent findings: Amylin is a pancreatic hormone acting to control energy homeostasis and body weight. Activity at the calcitonin and amylin receptors in the area postrema seems to – at least partly – be responsible for these effects of amylin. Both preclinical and early-stage clinical studies investigating long-acting amylin receptor analogues demonstrate beneficial effects on body weight in obesity. Cagrilintide, a novel amylin analogue suitable for once-weekly administration, is in phase II clinical development and has shown promising body weight reducing effects alone and in combination with the glucagon-like peptide 1 receptor agonist semaglutide. Summary: Long-acting amylin analogues have emerged as a possible pharmacotherapy against obesity, but more studies are needed to support the utility and long-term effects of this strategy in relevant populations.